Typology of Tahfidz Islamic Boarding School Curriculum in South Kalimantan - Rasyidi, Ahyar; Setiawan, Agus (SYAMIL: Journal of Islamic Education, 2021)
The purpose of this research is to describe the typology of the curriculum of tahfizh boarding schools in South Kalimantan. Curriculum as a guideline in learning at an educational institution, especially the tahfizd pesantren educational institution, has not been widely existed and researched so it is interesting to research. The method used is a qualitative method. Data analysis techniques that will be used in this research, namely "descriptive analytics" and in qualitative research in general starting from data collection, data reduction, data presentation, and conclusion or verification. The results showed that the entire tahfīzh institution of the Qur'an has the same expectations, in which the process of planning, organizing, mobilizing, and controlling people and other resources in achieving targeted goals effectively and efficiently" While the target to be achieved by tahfīzh institutions is the ability of learners to memorize the Qur'an. Although, there are many differences in methods and models in each institution of the Qur'anic Tahfidz. So, the curriculum of each institution may be different, but the results desired by the managers of all institutions are the same, namely acceleration or making it easier for everyone to memorize the Qur'an. The curriculum of the Tahfizh Al-Qur'an boarding school is compiled only to support the santri's memorization program, either from the model or method used in the memorization process, the book read, the educational process in the classroom, to the rules for the students. The education system in tahfizh boarding school is the same as the pesantren education system in general, namely there is a curriculum, learning methods, places to learn and others, it's just that there is something different from one cottage with another cottage so that it has its own uniqueness.